Progesterone Receptor Isoform Functions in Normal Breast Development and Breast Cancer - Kariagina, Anastasia (2008)
Progesterone acting through two isoforms of the progesterone receptor (PR), PRA and PRB, regulates proliferation and differentiation in the normal mammary gland in mouse, rat and human. Progesterone and PR have also been implicated in the etiology and pathogenesis of human breast cancer. The focus of this review is on recent advances in understanding the role of the PR isoform specific functions in the normal breast and in breast cancer. Also discussed is information obtained from rodent studies and their relevance to our understanding of the role of progestins in breast cancer etiology.